Social Production and Drugs Addiction Management among the Young Manual Workers in Northern Benin - IMOROU, ABOU-BAKARI (My University, 2019)
The objective of this research work is to analyze the social conditions inducing the emergence and management of performance-enhancing drugs addiction among the young manual workers in Northern Benin. This emerging socio-medical canker which tallies the strategies used to achieved better performance in production is rampant among the youth constantly involved in physical production. Indeed, any production needs physical and mostly human resource for tasks accomplishment. This also contributes to contextualizing labor valuation in a society whereby social success is appreciated in relation with individuals‟ capacities to produce, accumulate and assume responsibility. Eventually, this is about a context whereby arguments declassifying and stigmatizing largely draw on image of the laziness or incapability to assume anything. As such, family comes to play a crucial role in the constant pressure put on individuals by the social group with a view to urging him to labor. All the same, productivity becomes an individual and collective performance analyzer. From a socio-anthropological perspective, an in-depth description of individual performances and experiences in this study underscores the social impact of the youth drugs addiction. Besides, this research highlights the way those various drugs energize and nurture social unrests generated among the social groups under consideration. The ongoing thinking under cores the places of the social organs, values, perceptions as well as the various shifts noticed in the social life of individuals addicted to drugs.
Keywords: Performance-Enhancing Drugs; Tramol; Addiction; Hidden Use; Bénin.